2008
DOI: 10.1073/pnas.0801811105
|View full text |Cite
|
Sign up to set email alerts
|

Different assemblies of the DAM1 complex follow shortening microtubules by distinct mechanisms

Abstract: Mitotic chromosomes segregate at the ends of shortening spindle microtubules (MTs). In budding yeast, the Dam1 multiprotein complex supports this dynamic attachment, thereby contributing to accurate chromosome segregation. Purified Dam1 will track the end of a depolymerizing MT and can couple it to microbead transport in vitro. The processivity of such motions has been thought to depend on rings that the Dam1 complex can form around MTs, but the possibility that alternative coupling geometries contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
135
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(141 citation statements)
references
References 25 publications
6
135
0
Order By: Relevance
“…Together, these findings show that in fission yeast, Dam1 forms small speckles both on cytoplasmic MTs during interphase and kinetochores during mitosis. Similar small assemblies, called patches, also formed in vitro with recombinant ScDam1 complex (10,15,16). Hereafter, we refer to the small SpDam1 speckles as patches.…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, these findings show that in fission yeast, Dam1 forms small speckles both on cytoplasmic MTs during interphase and kinetochores during mitosis. Similar small assemblies, called patches, also formed in vitro with recombinant ScDam1 complex (10,15,16). Hereafter, we refer to the small SpDam1 speckles as patches.…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 99%
“…Also noteworthy, a Dam1 patch occasionally separated into smaller spots, followed by merging into one spot later (Fig. S3B), reminiscent of the ScDam1 patches in vitro (16)…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it was subsequently shown that ring formation is not required for microtubule depolymerization-driven motion of the Dam1 complex [133,134].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%